The Portrait of industrial Artefacts: The trigger of a new apreciation - Cabrera Vergara, María (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
This paper intends to acknowledge the essential role that photography has played in the generation of a new appreciation within the architectural discipline, triggered precisely by the portrait of some artefacts which, paradoxically, had been during decades completely overlooked by it: the industrial storage structures. The aim of this text is threefold: First, to retrace how the first unintentional portraits of industrial artefacts taken during the early years of the 20th century unleashed an aes- thetic fascination and transformed them into a fundamental source of inspiration for the new forms of architecture. Second, to examine how the later work of subsequent photographers of second half of the 20th century unveiled diverse conceptual facets of these industrial structures, and exposed their architectural nature. Finally, to evidence how this evolutionary process towards a conceptual interest contributed to challenge the parameters of what, till that moment, defined what was assumed as a valid source of interest and inspiration to the architectural discipline.